Binding characteristics study for dengue virus non-structural protein 1 of antigen and its antibody by using circular dichroism technique - N. A., Yusoff; N., Soin; N., Abd Rahman; R. N. Z., Raja Abd Rahman; M. K. B., Abd Kahar (Institute of Electrical and Electronic Engineers (IEEE), 2011)
Link to publisher's homepage at http://ieeexplore.ieee.org/